BIM Implementation for Storing, Sharing and Capturing Knowledge in Indonesian Project Construction - Utama, Singgih Fitra; Negara, Kartika Puspa; Wijatmiko, Indradi (Civil and Environmental Science Journal (CIVENSE), 2023)
BIM as a digital representation of assets has been used to facilitate design, construction, and operation process to form a reliable basis for decisions. While knowledge is part of the company's assets, knowledge will be maintained in the system so that it may be recalled if needed if BIM is used to document, store, and distribute knowledge more easily. This study will determine how BIM adoption supports knowledge storage, knowledge share, and knowledge capture in Indonesian construction projects. Data was obtained by interview and analysed using qualitative method. The results showed that large state-owned construction companies in Indonesia had implemented BIM-based knowledge management to assist organisational knowledge management process, especially in knowledge capture, storage and share on several projects, and reduce knowledge loss due to time lapse. Finding also shows that knowledge created in a project is centralised in one model, and lessons or knowledge can be grouped with BIM user preferences.